The dynamics of Carat Indonesia's solidarity in anonymous interactions on X - Nabila Zikri Ramadhanti; Nanik Rahmawati; Nikodemus Niko (Priviet Social Sciences Journal, 2025)
This study aims to understand how solidarity is formed and maintained among members of the Boy Group Seventeen fan community, Carat Indonesia, on social media X (formerly Twitter,we use the term "social media platform X" throughout this manuscript) despite the anonymity of interactions. It explores the paradox of solidarity emerging without personal identity disclosure, challenging the conventional notion that solidarity is trust-based. This study employs a qualitative method with a netnography approach to provide an in-depth analysis of solidarity dynamics in online communities. Informants were selected using a purposive sampling technique to provide relevant insights into this phenomenon. The study reveals that anonymous identities do not hinder the formation of trust among Indonesian Carat members on social media X. Instead, trust is built by assessing the track record of account owners. The solidarity that emerges aligns with Durkheim’s concept of mechanical solidarity, which is characterized by shared interests, low division of labor, high collective consciousness, and repressive norms. This study focused solely on the Carat Indonesia community on social media platform X, limiting its generalizability to other online fan communities. Additionally, reliance on online observations and interactions may not fully capture offline aspects of solidarity. This study contributes to the understanding of online community solidarity by demonstrating how trust and cohesion can be established despite anonymity. This extends Durkheim’s theory of social solidarity to digital interactions, providing insights into the mechanisms of mechanical solidarity in contemporary online spaces.